Lysine 68 acetylation directs MnSOD as a tetrameric detoxification complex versus a monomeric tumor promoter - Zhu, Yueming (Nat Commun, 2019)
Manganese superoxide dismutase (MnSOD) functions as a tumor suppressor; however, once tumorigenesis occurs, clinical data suggest MnSOD levels correlate with more aggressive human tumors, implying a potential dual function of MnSOD in the regulation of metabolism. Here we show, using in vitro transformation and xenograft growth assays that the MnSOD-K68 acetylation (Ac) mimic mutant (MnSOD(K68Q)) functions as a tumor promoter. Interestingly, in various breast cancer and primary cell types the expression of MnSOD(K68Q) is accompanied with a change of MnSOD’s stoichiometry from a known homotetramer complex to a monomeric form. Biochemical experiments using the MnSOD-K68Q Ac-mimic, or physically K68-Ac (MnSOD-K68-Ac), suggest that these monomers function as a peroxidase, distinct from the established MnSOD superoxide dismutase activity. MnSOD(K68Q) expressing cells exhibit resistance to tamoxifen (Tam) and cells selected for Tam resistance exhibited increased K68-Ac and monomeric MnSOD. These results suggest a MnSOD-K68-Ac metabolic pathway for Tam resistance, carcinogenesis and tumor progression.